(untitled) (Research, Society and Development, 2022)
The objective of the research was to describe the influence of Manual Therapy on the main symptoms of Temporomandibular Joint Disorders. Such dysfunctions are problems that affect and compromise the functioning of the Temporomandibular Joint, a complex joint located in the skull and responsible, mainly, for chewing and speech movements, which can culminate in pain and damage to the quality of life of the people affected. The descriptive and transversal research, for its execution, counted on the application of Manual Therapy, during 4 days of sections, arranged in 4 weeks, in a group of 6 volunteers aged between 19 and 45 years, who presented signs of Temporomandibular Disorders, this being the main criterion for participation, and the application of the Anamnestic Questionnaire, Visual Analogue Scale and Questionnaire and Mandibular Functional Limitation Index, to assess improvement in the signs of Temporomandibular Disorders, in this case, pain and functions. The research methodology had a quantitative approach. The results obtained were statistical findings of pain relief from the second section of application of Manual Therapy and improvement in the functional status of the Temporomandibular Joint. In conclusion, the study volunteers had pain relief and improvement of movements performed by the Temporomandibular Joint, which demonstrates the effectiveness of Manual Therapy to alleviate the symptoms of Temporomandibular Disorders.